'Fresh seal blood looks like beauty and life': #Sealfies and subsistence in Nunavut. Issue 4 (April 2019) - Searles, Edmund Q
Abstract : In this paper, I analyse the various functions, meanings and affects associated with seal hunting, eating and sharing seal meat, wearing sealskin clothing and posting #sealfies. Drawing on several decades of research with hunting and gathering families in the eastern Canadian Arctic, and starting with the cultural premise that hunting seals unites the worlds of humans, animals and spirits, I argue that the seal is a prominent metaphor for the Inuit self. By extension, I examine how Inuit use #sealfies as an extension of other subsistence practices, as a way of making identity (personal and collective), and as a way of countering the negative stereotypes used by animal rights activists to condemn hunting in general. #Sealfies have become an important resource in the subsistence toolkit of contemporary Nunavut Inuit foragers, providing an effective platform for defending their foraging traditions and for creating a meaningful and modern identity.